Supporting the selection of digital resources for classroom-based teaching activities - Atif, Y.; Sampson, Demetrios; Harous, S. (2013)
Digital systems are offering opportunities to find, select, adapt, and use digital educational resources for teaching and learning which are openly available in the Web. As a result, innovative technology-supported classroom-based activities are widely anticipated by key stakeholders in formal education, namely, students, parents, education managers and policy makers. This puts a tremendous pressure on teachers and instructors to exploit digital resources in their daily classroom activities. Re-using available teaching resources is currently a major trend worldwide. This creates the need for tools that can support teachers in finding, and selecting appropriate digital resources for populating their lesson plans in school classrooms. Such tools can facilitate teaching processes to adopt technology-supported instructional strategies in a cost effective manner. In order to be able to build such tools, it is important to devise and study methods that can support teachers in discovering and selecting appropriate digital resources to populate their classroom-based teaching activities, taking into consideration important parameters of classroom-based instruction, such as time constraints and class population. To this end, in this paper we propose a design-to-time classroom-based teaching model and a time-adjusted lesson planning method that incorporates a classroom-constrained selection algorithm for digital resources available in Learning Object Repositories. We also evaluate the performance of the proposed algorithm. © 2013 IEEE.